2017
DOI: 10.15359/revmar.9-1.2
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de las poblaciones de caballitos de mar en diferentes zonas de la costa norte de las regiones occidental y central de Cuba

Abstract: Los caballitos de mar son peces ornamentales de gran interés para las exhibiciones en el Acuario Nacional de Cuba, por lo que se propuso valorar el estado actual de las poblaciones naturales de las especies Hippocampus reidi (Ginsburg, 1933) e Hippocampus erectus (Perry, 1810) en diferentes zonas de la costa norte de las regiones occidental y central de la isla. Se llevaron a cabo censos visuales mediante buceo libre, utilizando el método de transectos lineales, entre marzo del 2007 y marzo del 2010. Para la c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…We found a high population density of H. reidi on northern Guaíba island, which was in fact the highest density ever recorded for this species anywhere in the world (Dias & Rosa, 2003;Rosa et al, 2007;Freret-Meurer & Andreata, 2008;Mai & Rosa, 2009;Mai & Velasco, 2012;Oliveira & Freret-Meurer, 2012;Aylesworth et al, 2015;Gutiérrez et al, 2017;Freret-Meurer et al, 2018b). Studies on the coasts of Brazil (Rosa et al, 2007) and Cuba (Gutiérrez et al, 2017) have reported mean densities of between 0. Lagoon (Garcia & Vieira, 2001;Possamai et al, 2018), and in other areas around the world, including Peru (Arntz & Fahrbach, 1996;Lehodey et al, 1997), the Galapagos Islands, Clipperton Atoll and Baja California (Ruttenberg, 2000;Victor et al, 2001).…”
Section: Density Shift Across Time During the El Niñomentioning
confidence: 45%
See 1 more Smart Citation
“…We found a high population density of H. reidi on northern Guaíba island, which was in fact the highest density ever recorded for this species anywhere in the world (Dias & Rosa, 2003;Rosa et al, 2007;Freret-Meurer & Andreata, 2008;Mai & Rosa, 2009;Mai & Velasco, 2012;Oliveira & Freret-Meurer, 2012;Aylesworth et al, 2015;Gutiérrez et al, 2017;Freret-Meurer et al, 2018b). Studies on the coasts of Brazil (Rosa et al, 2007) and Cuba (Gutiérrez et al, 2017) have reported mean densities of between 0. Lagoon (Garcia & Vieira, 2001;Possamai et al, 2018), and in other areas around the world, including Peru (Arntz & Fahrbach, 1996;Lehodey et al, 1997), the Galapagos Islands, Clipperton Atoll and Baja California (Ruttenberg, 2000;Victor et al, 2001).…”
Section: Density Shift Across Time During the El Niñomentioning
confidence: 45%
“…We found a high population density of H. reidi on northern Guaíba island, which was in fact the highest density ever recorded for this species anywhere in the world (Dias & Rosa, 2003; Rosa et al ., 2007; Freret‐Meurer & Andreata, 2008; Mai & Rosa, 2009; Mai & Velasco, 2012; Oliveira & Freret‐Meurer, 2012; Aylesworth et al ., 2015; Gutiérrez et al ., 2017; Freret‐Meurer et al ., 2018b). Studies on the coasts of Brazil (Rosa et al ., 2007) and Cuba (Gutiérrez et al ., 2017) have reported mean densities of between 0.026 and 0.306 ind m −2 , while the present study recorded a mean density of 0.55 ind m −2 , peaking at 1.42 ind m −2 in 2016. It is important to note that the same area was studied by Freret‐Meurer et al .…”
Section: Discussionmentioning
confidence: 99%
“…Population densities of several species of seahorses in natural environments have varied as follows: 0.00047 to 0.51 individuals/m 2 (Curtis & Vincent, 2005;Silveira, 2005;Rosa et al, 2007;Mai & Velasco, 2011;Pastor Gutiérrez et al, 2017;Woodall et al, 2018;Freret-Meurer et al, 2018). In the present work, there was a clear decrease in natural stocks in the two areas surveyed.…”
Section: Density Sex Ratio and Population Structure Inmentioning
confidence: 45%
“…How can we say that it is an excess? According to several studies carried out with species of the family Syngnathidae, the population structure of seahorses is often represented by a 1:1 sex ratio, similar size between sexes and sexual dimorphism, and proportionally with few juveniles (Perante et al, 2002;Bell et al, 2003;Moreau & Vincent, 2004;Silveira, 2005;Curtis & Vincent, 2006;Gristina et al, 2015;Pastor Gutiérrez et al, 2017) Hippocampus capensis Boulenger 1900, is a rare example of a marine fish listed as Endangered by the IUCN because of its limited range and habitat vulnerability. It is restricted to four estuaries on the southern coast of South Africa.…”
Section: Mean Height At Brood Pouch Formation and Mean Height At Firs...mentioning
confidence: 99%